Reconfigurações de modelos de gestão: o caso das empresas familiares no Brasil - Soulé, Fernanda Veríssimo (Universidade Federal de São Carlos, 2020)
This study examines the reconfiguration in the moral structures that support family business models of management, relating them to the transformations in the ideologies of capitalism. Studies in the sociological institutionalism that investigate historical changes in models of management mostly describe dominant models in different periods. From this lens, the family model would have lost its ability to provide justifications for mobilizing and engaging individuals. However, this research demonstrates that family businesses not only survived but went through processes of reorganization that allowed them to remain central to the functioning of capitalism. Inspired by Luc Boltanski’s sociology of critical capacity, I assessed the changes over time in the normative content about and for these companies using three datasets. Supported by Voyant, Mallet, R-Studio, and Prospero software, I analyzed 51 Brazilian handbooks focused on family businesses published from 1978 to 2018. I also carried out participant observation in twelve events aimed at family businesses and nine semi-structured interviews with key actors, as executives, heirs, consultants, and academics, in the United States and Brazil. I identified instruments and moralities that allowed family businesses to remain important over three periods. In the first, there was the emergence of the category of family business in the social space of management, which is associated with industrial capitalism. The second period was marked by the influence of financialization in the companies’ and families’ way of organizing. Finally, the centrality of connectionist capitalism in the current reconfiguration of this model became dominant in the last period. The results revealed that the changes in the most relevant forms of value in capitalism reflected in the emergence of new concepts in the social space of family businesses, such as professionalization, governance, holding, family office, entrepreneurship, networks, and legacy. Overall, the research concludes that dominant models of management do not necessarily exclude former ones. When they are able to reshape, as in the case of family businesses, they may become more robust.
Reconfigurations of models of management: the case of family business in Brazil
Keywords: Empresas familiares; Modelos de gestão; Espíritos do capitalismo; Luc Boltanski; Ciências sociais computacionais; Family businesses; Models of management; Spirits of capitalism; Computational social sciences; CIENCIAS HUMANAS::SOCIOLOGIA::OUTRAS SOCIOLOGIAS ESPECIFICAS